Studi Deskriptif Kelengkapan Kode External Cause Berdasarkan ICD-10 pada Kasus Kecelakaan Lalu Lintas Di RSUD Brigjend. H. Hasan Basry Kandangan - Nirma Yunita; Faizah Rahayu (Jurnal Kesehatan Indonesia, 2020)
An external cause is the reason for a medical condition that can be associated with certain objects or processes that are caused by something outside the body. The constraint in completing the external cause code is the lack of knowledge and training of health workers. This study aims to determine the completeness of the external cause code based on ICD-10 in traffic accident cases. This research deskriptif uses descriptive research with qualitative and quantitative approaches. Subjects in research are 3 respondents, namely the main informant is a coder, the second informant is the emergency room doctor and the third informant is the head of the installation medical record. The object of the research is the medical records of traffic accidents berjumlah 38 medical records. Data collection techniques using triangulation of observational data, interviews and document collection. The results of the study show the characteristics of health workers related to the completeness of external cause codefication based on the average length of work and length of work and competence, Completeness Codification of external cause diagnosis in traffic accident cases from 38 documents medis medical records of traffic accident patients are incomplete, Obstacles in implementing external cause codefication in traffic accident cases health workers do not know and do not use an external cause code and there is no coding evaluation.